Cyclists as the element that creates the city - Katarzyna Szmygin (Budownictwo i Architektura, 2016)
The active participation of cyclists in the transformation of urban structures is becoming a commonly discussed subject nowadays. More bike lanes are being constructed, city bike stations, as well as grade-separated crossroads for cyclists and drivers are being created. Cyclists have been increasingly taken into consideration in the changes taking place within the city. Along with the revolution introduced by a Danish architect and urban planner Jan Gehl has changed thinking about cyclists. All of his regeneration and restoration projects focused primarily on structures that allow cyclists and pedestrians move without any obstacles. Article will discuss the founding of the cyclists-friendly city, the polish requirements for cycling infrastructure, as well as show examples of Polish and foreign properly designed solutions.